2013
DOI: 10.1177/1060028013505427
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Continuous Infusion for Refractory Status Epilepticus in a Patient With Anticonvulsant Hypersensitivity Syndrome

Abstract: This is the first case report to describe a successful transition to a ketamine infusion in a patient with AHS and transaminitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
11
1
Order By: Relevance
“…Although not FDA approved for the management of SE, ketamine has been described as an adjunctive agent in patients unable to attain seizure control with benzodiazepines, such as midazolam, or propofol. [2][3][4][5][6][7][8][9][10] To the best of our knowledge, the use of ketamine as an adjunct to barbiturate coma has not been reported in literature. In the following cases, we describe using continuous ketamine in combination with pentobarbital to achieve seizure control and decrease the dose and duration of pentobarbital coma.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Although not FDA approved for the management of SE, ketamine has been described as an adjunctive agent in patients unable to attain seizure control with benzodiazepines, such as midazolam, or propofol. [2][3][4][5][6][7][8][9][10] To the best of our knowledge, the use of ketamine as an adjunct to barbiturate coma has not been reported in literature. In the following cases, we describe using continuous ketamine in combination with pentobarbital to achieve seizure control and decrease the dose and duration of pentobarbital coma.…”
Section: Introductionmentioning
confidence: 74%
“…1,11,12 Published case reports and case series describe successful use ketamine infusions to augment the action of continuous antiepileptic drugs, such as midazolam and propofol, in RSE. [2][3][4][5][6][7][8][9][10] In a recent systematic review on the effectiveness of NMDA receptor antagonists in RSE, ketamine was noted to achieve a positive response in 56.5 % adult patients. Adverse events related to ketamine in these patients were rare.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Case reports suggest the efficacy of IV ketamine infusion even in cases where traditional GABAergic anesthetics fail. [50][51][52] Ketamine has theoretical advantages, including its potential to be neuroprotective via modulation of N-methyl-D-aspartate (NMDA) activity and its lack of cardiovascular side effects. 48 A multicenter retrospective study concluded that ketamine infusion was safe and potentially efficacious when administered via a loading dose followed by a continuous infusion.…”
Section: Refractory Status Epilepticus and Superrefractory Status Epimentioning
confidence: 99%